Six weeks of either EPA-rich or DHA-rich Omega-3 supplementation alters submaximal exercise physiology in endurance trained male amateurs - Blannin, Andrew; Boulton, George; Thielecke, Frank (Frontiers in Nutrition, 2025)
PurposeSupplementation with Omega-3 fatty acids such as Docosahexaenoic acid (DHA) and/or Eicosapentaenoic acid (EPA) have been shown to lower submaximal exercise heart rate (HR) and whole-body oxygen consumption along with other positive exercise physiology adaptations. However, the impact of supplementation on exercise physiology is inconsistent. This could be due to existing study heterogeneity, including inconsistent use of EPA or DHA supplements. The current study aimed to investigate if EPA-rich or DHA-rich supplements are equally efficient at modifying physiological responses to submaximal exercise and potentially improving performance.MethodsFifty-five endurance trained amateurs participated in a submaximal exercise test followed by a 24 km time trial (TT) before and after a six-week supplementation period. Participants were supplemented with either 3 g/day EPA-rich fish oil, DHA-rich algae oil, or a coconut oil placebo. Omega-3 index, submaximal exercising HR, rating of perceived exertion (RPE), respiratory exchange ratio (RER), and TT performance were all assessed.ResultsThe EPA-rich and DHA-rich supplements significantly increased the Omega-3 index, whereas the placebo supplement had no effect. Statistically significant changes between pre-and post-supplementation were found in submaximal exercise physiology. Both EPA-rich and DHA-rich supplementation lowered submaximal exercising HR (∆ = −4, p = 0.005) (∆ = −9, p ≤ 0.001) and RPE (∆ = −0.7, p ≤ 0.001) (∆ = −0.9, p ≤ 0.001), while only EPA-rich supplementation increased RER (∆ = +0.03, p ≤ 0.001). Change in Omega-3 index inversely correlated with both change in submaximal exercising HR (RHO = −0.43, p = 0.007) and RPE (RHO = −0.40, p = 0.013). TT performance improved in all three conditions, but there were no significant differences in the gains across the three conditions.ConclusionThis study adds further evidence that both EPA and DHA can alter submaximal exercise physiology, but further research is required to determine their effects on exercise performance outcomes.